1995
DOI: 10.1055/s-0038-1653843
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Human Platelets to Plasmin Results in the Expression of Irreversibly Active Fibrinogen Receptors

Abstract: SummaryAlthough plasmin can trigger strong platelet responses such as shape change and exocytosis of internal granules, limited platelet aggregation is induced by this proteinase, owing to its capacity to rapidly proteolyse secreted adhesive proteins. In this context, we have investigated the state of activation of the fibrinogen receptor, the integrin αIIbβ3, on platelets exposed to plasmin. Following incubation with plasmin at 37 °C, washing, and resuspension, platelets exhibit a moderate, low-velocity aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
4
20
0
1
Order By: Relevance
“…The mechanism of platelet activation or inhibition by plasmin is poorly understood. Plasmin at a concentration in excess of 1 caseinolytic unit/ml triggers platelet aggregation at 37°C through direct or indirect activation of the integrin glycoprotein IIb/ IIIa (Loscalzo et al, 1995;Rabhi-Sabile and Pidard, 1995). Plasmin may promote platelet activation by cleaving the seven transmembrane thrombin receptor to expose the tethered ligand containing the SFLLRN sequence, which directly activates platelets in the same manner as thrombin (Kuliopulos et al, 1999).…”
mentioning
confidence: 99%
“…The mechanism of platelet activation or inhibition by plasmin is poorly understood. Plasmin at a concentration in excess of 1 caseinolytic unit/ml triggers platelet aggregation at 37°C through direct or indirect activation of the integrin glycoprotein IIb/ IIIa (Loscalzo et al, 1995;Rabhi-Sabile and Pidard, 1995). Plasmin may promote platelet activation by cleaving the seven transmembrane thrombin receptor to expose the tethered ligand containing the SFLLRN sequence, which directly activates platelets in the same manner as thrombin (Kuliopulos et al, 1999).…”
mentioning
confidence: 99%
“…Other biomaterial-independent factors contributing to platelet activation (and subsequent dysfunction) after CPB include heparin at the doses used for CPB [92], activated complement [93], plasmin [94] and a variety of other soluble blood elements. Platelets adhere to binding sites located on surface-adsorbed brinogen and form aggregates [95].…”
Section: F D Rubensmentioning
confidence: 99%
“…2. Immunoblotting sion was continuously recorded and platelet aggregation expressed as analysis of cell-associated TSP-1 performed under reducing a percentage of the maximal variation in LT [19]. At the given time conditions indicated that TSP-1 was rapidly proteolyzed durpoints, the enzymic activity of CG was blocked by the addition of 1 mmol/1 PMSF and 200 gg/ml SBTI [12], whereas cx-thrombin was ing activation ( Fig.…”
Section: Preparation Of Isolated Human Plateletsmentioning
confidence: 99%
“…2 indicated that the conversion of mixed with 40 gl of a solution of 0.1 moll1 EDTA to stop exocytosis TSP-1 into TSP-1 f closely paralleled the rates of a-granule and centrifuged at 12000×g for 4 min. The supernatant, and an exocytosis and platelet aggregation (indicated at the bottom aliquot of the unsedimented platelet suspension, were kept at of the figure), with TSP-lf corresponding to 12, 40, and 81% -20°C until they were processed for the measurement of secreted I 3-thromboglobulin (13-TG) [19]. This was done using a commercial ELIof the total TSP-l-reactive material at 1, 3, and 5 min of SA (Diagnostica Stago, Asni~res, France) following the manufacactivation, respectively ( Fig.…”
Section: Preparation Of Isolated Human Plateletsmentioning
confidence: 99%
See 1 more Smart Citation